Effect of ablation of complex fractionated atrial electrogram on vagal modulation in dogs - Zhang, Shu-Long; Dong, Ying-Xue; Jiang, Peng; Gao, Lian-Jun; Cha, Yong-Mei; Packer, Douglas L; Xia, Yun-Long; Yin, Xiao-Meng; Chang, Dong; Yang, Yan-Zong (Chinese medical journal, 2010)
Background Clinical observations have shown that the complex fractionated atrial electrogram （CFAE） associates with ganglionated plexus activity in the cardiac autonomic nervous system. This study aimed to investigate the impact of CFAE ablation on vagal modulation to atria and vulnerability to develop atrial fibrillation （AF）. Methods Ten adult mongrel dogs were involved. Cervical sympathovagal trunks were decentralized and sympathetic effects were blocked. CFAE was color tagged on the atrial 3-dimensional image and ablated during AF induced by S1S2 programmed stimulation plus sympathovagal trunk stimulation. Atrial effective refractory period （ERP） and vulnerability window （VW） of AF were measured on baseline and at vagal stimulation at 4 atrium sites. Serial tissue sections from ablative and control specimens received hematoxylin and eosin staining for microscopic examination. Results Most CFAE areas were localized at the right superior pulmonary quadrant, distal coronary sinus （CS~） quadrant, and proximal coronary sinus （CSp） quadrant （21.74%, separately）. Sinus rhythm cycle length （SCL） shortening did not decrease significantly after ablation at the sites, including right atrial appendage, left atrial appendage, CSd, and CSp （P 〉0.05）. ERP shortening during vagal stimulation significantly decreased after ablation （P 〈0.01）; the VW to vagal stimulation significantly decreased after ablation （P 〈0.05）. The architecture of individual ganglia altered after ablation. Conclusions CFAE has an autonomic basis in dogs. The decreased SCL and ERP shortening to vagal stimulation after CFAE ablation demonstrate that CFAE ablation attenuates vagal modulation to the atria, thereby suppressing AF mediated by enhanced vagal activity. CFAE ablation could suppress AF mediated by enhanced vagal activity.